Effectiveness of anaesthesia- Nurse-Administered Sedation Protocols in Minor Surgical Procedures - Tariq Homeed O AL Fahmi; Nasser Ali Nasser Zbragi; Mariam Ali Mushabab; Ahmad Mohmad Z Alansari; Mansour Abdrabuh Ali Alzahrani; Subha Bin Mohammed Alzahranl; Suha Mhamoud Siraj Halwani; Alaa Attehallah Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The administration of sedation during minor surgical procedures is a foundational element of patient-centered care, designed to optimize comfort, alleviate anxiety, and facilitate a seamless surgical experience. Nurse-administered sedation protocols have emerged as an effective mechanism for achieving controlled sedation in outpatient environments, especially for procedures that do not necessitate general anesthesia. This review evaluates the effectiveness of such nurse-administered protocols, focusing on their multifaceted benefits, potential risks, and overall impact on patient outcomes and satisfaction. Incorporating current literature, including comparative studies and clinical guidelines, this analysis presents an evidence-based perspective on the crucial role of nursing professionals in the administration of sedation. Emphasis is placed on critical aspects such as sedation depth, patient satisfaction, and the incidence of complications. The findings suggest that when conducted in accordance with established protocols and guidelines, nurse-administered sedation can be both a safe and effective option, significantly contributing to positive patient experiences during minor surgical interventions.